2013
DOI: 10.1017/jmo.2013.10
|View full text |Cite
|
Sign up to set email alerts
|

Three-way interaction effects of workaholism on employee well-being: Evidence from blue-collar workers in New Zealand

Abstract: Workaholism is an important workplace phenomenon that has received less empirical testing than might be expected. This study of 100 New Zealand blue-collar workers tested whether three dimensions of the workaholism triad: work involvement, drive to work and work enjoyment were related to anxiety, depression and insomnia, and in the majority this was supported. Work involvement was positively related to all outcomes, while work enjoyment was negatively related. Drive to work was positively related to anxiety an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
(89 reference statements)
1
10
0
Order By: Relevance
“…Besides this comprehensive study, there are a few others that addressed some psychological symptoms (mostly somatization, depression, anxiety, or generic mental health) and usually did not address psychopathology as an antecedent of Workaholism (e.g., Bartcazk and Ogińska-Bulik, 2012 ; Nie and Sun, 2016 ; Andreassen et al, 2018 ). Moreover, only a few studies included Work Engagement in the analyses (e.g., Andreassen et al, 2007 ; Haar and Roche, 2013 ). In sum, as previously reviewed by Loscalzo and Giannini (2020b) , (i) There are a few studies supporting the association between Workaholism and somatization, anxiety, depression, attention deficit and hyperactivity disorder (ADHD), and OCD symptoms; (ii) There is preliminary evidence for ADHD and anxiety as predictors of Workaholism, in contrast with depression and OCD symptoms; (iii) Work Engagement is associated with lower somatization, anxiety, and depression, even if Shimazu et al (2018) found that higher levels of Work Engagement may harm mental health in the short-term (though this negative effect disappears, and it becomes positive, in the long-term).…”
Section: Introductionmentioning
confidence: 99%
“…Besides this comprehensive study, there are a few others that addressed some psychological symptoms (mostly somatization, depression, anxiety, or generic mental health) and usually did not address psychopathology as an antecedent of Workaholism (e.g., Bartcazk and Ogińska-Bulik, 2012 ; Nie and Sun, 2016 ; Andreassen et al, 2018 ). Moreover, only a few studies included Work Engagement in the analyses (e.g., Andreassen et al, 2007 ; Haar and Roche, 2013 ). In sum, as previously reviewed by Loscalzo and Giannini (2020b) , (i) There are a few studies supporting the association between Workaholism and somatization, anxiety, depression, attention deficit and hyperactivity disorder (ADHD), and OCD symptoms; (ii) There is preliminary evidence for ADHD and anxiety as predictors of Workaholism, in contrast with depression and OCD symptoms; (iii) Work Engagement is associated with lower somatization, anxiety, and depression, even if Shimazu et al (2018) found that higher levels of Work Engagement may harm mental health in the short-term (though this negative effect disappears, and it becomes positive, in the long-term).…”
Section: Introductionmentioning
confidence: 99%
“…Exhausted workers also might be more prone to negative work- and non-work-related attitudes, behaviors, and states (e.g., Barnes, 2012; Barnes, Miller, & Bostock, 2017; Crain, Brossoit, & Fisher, 2018; Schneider, Fulda, & Schulz, 2004). Restless nights and the resulting fatigue are especially prevalent when organizations and their work forces confront significant pressures, within or outside the workplace (Haar & Roche, 2013; Toker, Laurence, & Fried, 2015). Organization scholars and practitioners thus need insights into why some employees might be more likely than others to suffer from insomnia, as well as suggestions for tactics to limit the detrimental effects (Crain, Brossoit, & Fisher, 2018; Garcia, Bordia, Restubog, & Caines, 2018; Ng & Feldman, 2013; Ragins, Ehrhardt, Lyness, Murphy, & Capman, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Extant research into the determinants of sleep deprivation often cites individual factors such as age (Coombe, Epps, Lee, Chen, Imes, & Chasens, 2019), work involvement (Haar & Roche, 2013), and time spent at work or with family (Barnes, Wagner, & Ghumman, 2012), as well as organizational factors such as contract breaches (Garcia et al, 2018) or organizational changes (Rafferty & Jimmieson, 2017). Another pertinent non-work -related source of insomnia, with great relevance today, may be employees' fears about life-threatening viruses (Ahorsu, Lin, Imani, Saffari, Griffiths, & Pakpour, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Depression seems to be significantly related to workaholism, leading directly to work addiction (and vice versa) [ 68 , 91 , 92 ]. The relationship between workaholism and depression has been demonstrated in studies conducted in various professional and cultural contexts [ 66 , 69 , 70 , 93 , 94 ]. Haar and Roche [ 89 ] found that both work commitment and joy at work were associated with anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%